2016
DOI: 10.4314/jae.v20i1.4
|View full text |Cite
|
Sign up to set email alerts
|

Adoption of root and tuber technologies disseminated by the National Root Crops Research Institute in Anambra State

Abstract: The study examined

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 5 publications
(6 reference statements)
1
2
0
Order By: Relevance
“…These age distribution shows that majority of the respondents are still in their active stage of life, these young people are opened to new ideas and agricultural innovations been spread to them. This finding is in line with Ironkwe et al (2016), in a study about the adoption of roots and tubers technologies, showing that the majority of the respondents were between age 41-50 years old. An economic and productive age that can facilitate adoption of technologies.…”
Section: Socio-economic Characteristics Of the Potato Farmerssupporting
confidence: 90%
“…These age distribution shows that majority of the respondents are still in their active stage of life, these young people are opened to new ideas and agricultural innovations been spread to them. This finding is in line with Ironkwe et al (2016), in a study about the adoption of roots and tubers technologies, showing that the majority of the respondents were between age 41-50 years old. An economic and productive age that can facilitate adoption of technologies.…”
Section: Socio-economic Characteristics Of the Potato Farmerssupporting
confidence: 90%
“…The implication is that at this age, they are likely to be more responsive to vegetable production improvement programme in the study area. Older adults as a group tend to be slower than younger adults to adopt new technology (Ironkwe et al, 2016). Age is assumed to be a serious factor in of adoption of new innovation.…”
Section: Results and Discussion Socio-economic Characteristics Of The Farmersmentioning
confidence: 99%
“…In some cases, the characteristics of a technology play a significant role. Mignouna et al (2011) in Ironkwe, Ezebuiro and Ewuziem (2016) reported that the characteristic of a technology plays a critical role in the adoption decision process. They argued that farmers who perceive the technology being consistent with their needs and compatible to their environment are likely to adopt since they view it as a positive investment.…”
Section: Resultsmentioning
confidence: 99%